Early gas leakage detection and fire alarm system / Hannes Zuleikha Zaidi ... [et al.] - Zaidi, Hannes Zuleikha; Norli, Muhammad Hafizi; Abu Bakar, Nur Hidayah; Radzali, Rosfariza; Abd Rahim, Alhan Farhanah (2022)
The presence of gas leaks, gas tanks, and grease might aggravate fire in the Universiti Teknologi MARA Pulau Pinang (UiTMCPP) hotel kitchen. Gas leakages are sometimes detected late, and this may cause an explosion inside the kitchen. This project thus includes early gas leakage detection and a fire alarm system to prevent fire explosions in the hotel kitchen using gas sensors, temperature sensor and flame sensor. It is observed in the UiTMCPP hotel kitchen that there is no monitoring system to monitor current gas readings in the kitchen area. Thus, this project provides an LCD to monitor data on current temperature and gas leakage by displaying it on the LCD. When there is a gas leakage or fire, the alarm system will go off immediately and warn the user through the LCD, buzzer, and LED. The system is also equipped with an automatic shut-off valve for safety and gas shut-off control in the gas feed pipe. UiTMCPP hotel kitchen has been constantly used for activities that involve staff and students. This project is intended to serve as an early warning system if any dangerous situation occurs during their activities in the hotel kitchen. The methods used in this project are based on the Proteus Software for the simulation and Arduino Software for the coding. The PCB is designed and developed for the onboard connection of the system.